2002
DOI: 10.1103/physrevb.65.045312
|View full text |Cite
|
Sign up to set email alerts
|

Intensity correlated nonlinear photoluminescence spectra in undoped andp-doped GaAs and GaAs quantum wells

Abstract: We study the line shapes and excitation density dependence of the intensity correlated nonlinear ͑NL͒ photoluminescence ͑PL͒ spectra due to excitons and free electron-hole pairs in molecular beam epitaxy grown undoped and p-doped GaAs and GaAs quantum wells. The laser excitation intensity ͑I͒ is varied by nearly three orders of magnitude. The NL PL spectra show negative peaks at energies corresponding to free and bound excitons as I increases. These peaks do not diminish, but continue to increase with I up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The PL deconvolution suggested that the fwhm of the P3 increased with the inclement of the excitation power (see Supporting Information, Figure S2). This is because the free electron−hole pair PL began to appear at higher excitation power density . Moreover, the peak position of P3 was constant for the variation of the excitation power.…”
mentioning
confidence: 90%
“…The PL deconvolution suggested that the fwhm of the P3 increased with the inclement of the excitation power (see Supporting Information, Figure S2). This is because the free electron−hole pair PL began to appear at higher excitation power density . Moreover, the peak position of P3 was constant for the variation of the excitation power.…”
mentioning
confidence: 90%
“…where P L(τ, hω) is the time-integrated PL signal at an energy hω due to two-beam excitation with a delay τ between the corresponding pulses in the two beams and P L(0, hω) is the same quantity at τ = 0. This way of defining ECPL signal is different from the usual definition of ECPL signal found in the literature [18][19][20] but is simpler to interpret. 16 We measured PL spectra at different delays using high resolution CCD-spectrograph and calculated ECPL spectra numerically from the stored PL spectra.…”
Section: Methodsmentioning
confidence: 80%
“…This method, giving high spectral resolution, is different from the conventional ECPL measurements where the two beams incident on the sample are chopped (modulated) at different frequencies and the emitted PL signal (after being spectrally dispersed) is measured with a point detector at the sum or difference frequency, one wavelength at a time. [18][19][20] As per our definition, ECPL signal is zero at τ = 0 and should remain at zero at any other delay if there are no nonlinearities in the PL emission, as the total number of photons incident on the sample per second is independent of the delay between the pulses. A nonzero ECPL signal is indicative of nonlinearity in the emitted PL caused by various nonlinear processes such as phase space filling, band gap renormalization, spectral broadening and spectral diffusion, which determine carrier dynamics in semiconductors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Luminescence correlation is a powerful technique 6,[8][9][10][11][12][13][14][15] that has so far been underutilized due to difficulties in interpreting measurements involving time and energy integrated correlations of temporally and spectrally varying carrier density. 6 This problem of correlations can be avoided by time resolving the nonlinearity of the PL upconversion signal in a nonlinear crystal, in a similar fashion to time resolving the nonlinearity of pump-probe measurements.…”
Section: Model Setupmentioning
confidence: 99%